The Effect of Teacher's Motivation on Student Learning Activities in Islamic Education Lessons - Syarifatul Mutaqorribain; Asrori Asrori; Rusman Rusman (Universitas Pesantren Kh Abdul Chalim Mojokerto, 2022)
The purpose of this study was to measure the effect of teacher motivation on student learning activities in PAI subjects at SMPN 39 Surabaya. In this study, the authors conduct quantitative research which is a knowledge discovery process that uses data in the form of numbers as a tool to find information about what we want to know. Based on the research problem formulation and the existing data analysis process, the following conclusions can be drawn: All teachers at SMPN 39 Surabaya have a high enough effort to motivate their students, including in the fairly high category. This can be seen from the creativity, activity, and absorption of student learning outcomes which are quite high. The relationship of motivation given by the teacher to student learning activities at SMPN 39 Surabaya is very influential with a fairly good interpretation, this is evident from the results of Statistical Analysis Table 22 which shows that the calculated Chi SChi-Square = 28.36 is greater than the Chi-Square table obtained Fo > Ft 5% (5.99) means the significance (Ho is rejected) and in the interpretation table the Contingency Coefficient value is 0.664 so it is in the range of numbers between 0.600 to 0.800 with a fairly high (good) interpretation which indicates a fairly good relationship between the motivation given by the teacher and student learning activities at SMPN 39 Surabaya in the 2021/2022 academic year.